Online Testing Yields the Same Results as Lab Testing: A Validation Study With the False Belief Task - Schidelko, Lydia Paulin; Schünemann, Britta; Rakoczy, Hannes; Proft, Marina (Frontiers in Psychology, 2021)
Recently, online testing has become an increasingly important instrument in developmental research, in particular since the Covid-19 pandemic that made in-lab testing impossible. However, online testing comes with two substantial challenges. First, it is unclear how valid results of online studies really are. Second, implementing online studies can be costly and/or require profound coding skills. This article addresses the validity of an online testing approach that is low-cost and easy to implement: The experimenter shares test materials such as videos or presentations via video-chat and interactively moderates the test session. To validate this approach, we compared children’s performance on a well-established task, the change-of-location false belief task, in an in-lab and online test setting. In two studies, 3- and 4-year-olds received online implementations of the false belief version (Study 1) and the false and true belief version of the task (Study 2). Children’s performance in these online studies was compared to data of matching tasks collected in the context of in-lab studies. Results revealed that the typical developmental pattern of performance in these tasks found in in-lab studies could be replicated with the novel online test procedure. These results suggest that the proposed method, which is both low-cost and easy to implement, provides a valid alternative to classical in-person test settings.